Comparing ischemic cardiovascular effectiveness and safety between individual SGLT-2 inhibitors and DPP-4 inhibitors in patients with type 2 diabetes: a nationwide population-based cohort study - Kim, Hayeon; Seo, Jun-Ho; Nam, Jin Hyun; Lim, Yejee; Choi, Kyung Hee; Kim, Kyungim (Frontiers in Pharmacology, 2024)
Objectives: This study compared the ischemic cardiovascular events (iCVEs) effectiveness and safety of initiating empagliflozin or dapagliflozin with those of dipeptidyl peptidase-4 inhibitors (DPP-4is), as well as the comparative effects between empagliflozin and dapagliflozin. Methods: Using data from the National Health Insurance Service in Korea, patients with type 2 diabetes mellitus (T2DM) who were newly prescribed empagliflozin, dapagliflozin, or DPP-4is from 2016 to 2019 and who did not have a recent CVE history were included. A Cox proportional hazards regression model was used to estimate the adjusted hazard ratio (aHR) with 95% confidence intervals (CIs) for iCVEs and safety events. Results: Empagliflozin and dapagliflozin significantly reduced the risks of ischemic stroke (aHR 0.568, 95% CI 0.408–0.791; aHR 0.612, 95% CI 0.476–0.786, respectively) and all-cause mortality (aHR 0.590, 95% CI 0.442–0.788; aHR 0.730, 95% CI 0.603–0.884, respectively) compared with DPP-4is. Initiating dapagliflozin or empagliflozin was associated with significantly lower incidence of severe hypoglycemia, bone fracture, urinary tract infection, and acute kidney injury than that of DPP-4is. No significant differences were observed between empagliflozin and dapagliflozin in iCVEs and most safety outcomes. Conclusion: Empagliflozin and dapagliflozin showed significant preventive effects on ischemic stroke and all-cause mortality compared with DPP-4is in patients with T2DM, and their protective effects were similar. Both empagliflozin and dapagliflozin were not related to the harmful effects on most safety events. These results suggest that it may be beneficial to initiate empagliflozin or dapagliflozin for ischemic stroke prevention in patients with T2DM. However, further validation studies, such as randomized controlled trials, are needed to generalize these results.